2018
DOI: 10.1101/471409
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Peripheral blood exosomes pass blood-brain-barrier and induce glial cell activation

Abstract: Background: Exosomes are involved in intracellular communication and contain proteins, mRNAs, miRNAs, and signaling molecules. Exosomes were shown to act as neuroinflammatory mediators involved in neurodegenerative diseases including Alzheimer's disease (AD), Parkinson's disease (PD), amyotrophic lateral sclerosis (ALS). Brain aging has been associated to increased neuroinflammation. In addition, a decreased extracellular vesicle concentration was observed in aging tissues. The specific mechanisms how exosomes… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…However, the relative abundance of astrocyte α-syn arising from different sources (i.e., neuronal, peripheral, or endogenously expressed) remains to be determined. Regardless of what proportion of astrocytic α-syn is derived from peripheral sources, in agreement with our observation, a recent study demonstrated evidence that peripheral injection of blood EVs derived from aged mice activate astrocytes [55], further indicating that astrocytes play a critical role in response to peripheralderived EVs. In addition, stroke-induced enhanced BBB permeability promotes EVs and pro-inflammatory factors passing through the BBB, resulting in abnormal activation of astrocytes [59,103].…”
Section: Implications Of Peripheral α-Syn Contribution To Parkinson'ssupporting
confidence: 92%
“…However, the relative abundance of astrocyte α-syn arising from different sources (i.e., neuronal, peripheral, or endogenously expressed) remains to be determined. Regardless of what proportion of astrocytic α-syn is derived from peripheral sources, in agreement with our observation, a recent study demonstrated evidence that peripheral injection of blood EVs derived from aged mice activate astrocytes [55], further indicating that astrocytes play a critical role in response to peripheralderived EVs. In addition, stroke-induced enhanced BBB permeability promotes EVs and pro-inflammatory factors passing through the BBB, resulting in abnormal activation of astrocytes [59,103].…”
Section: Implications Of Peripheral α-Syn Contribution To Parkinson'ssupporting
confidence: 92%
“…The BBB restricts large molecule drug delivery, as well as 98% of small molecule drug delivery, which poses an issue for many therapeutic platforms [31]. However, exosomes have been shown in multiple studies to cross the BBB and deliver a therapeutic payload, making them an advantageous platform in regenerative medicine as well as treatment of neurological disorders [32,33]. All of these factors make exosomes an ideal vehicle for drug delivery for many applications, including drug delivery in the treatment of various diseases including heart disease.…”
Section: Exosomes For Drug Delivery Purposesmentioning
confidence: 99%
“…Our present study verified the exosome role in transporting NEAT1 into the cerebral cortex through BBB, consistent with that reported by other researchers fz. Morales-Prieto et al [33] indicated that exosomes could pass through BBB and act on glial cell activation. Reynolds et al [34] revealed that human microglial cells exosomes cross the BBB and are efficient delivery vehicles to the CNS.…”
Section: Discussionmentioning
confidence: 99%